Marker duster / Mohd Fairuz Mohd Zaid … [et al.] - Mohd Zaid, Mohd Fairuz; Ramin, Siti Nor Zaharah; Abd Razak, Nurhazira; Ibrahim, Nurul Najwa; Nordin, Nur Atiqah (Research Innovation Business Unit, 2014)
The marker duster comes with a two in one marker, a marker pen with a duster at the side of the marker. This portable marker will be easier for the users to clear the whiteboard as the duster is in the marker. This marker duster is very useful by educators and in the corporate environment. Novelty. Novelty represents originality and as such can distinguish between the creation of new knowledge and the adoption and use of existing knowledge. The novelty of our product is in our own innovation. It is hoped that our innovation benefits educators and has the potential for commercialisation (IP).